Road construction - Zulkifli, 'Aini Izzati (Universiti Teknologi MARA, Perak, 2019)
A road is a route or way on land between two places that has been improved to allow travel by foot or motor vehicle such as car, motor and bicycle. Roads are the major channel for transportation to carry goods and passengers. The objectives of this research is to explore the construction of road in Taman Cenderawasih, Mukim Naga, Kedah. It will focus on method of road construction and its equipment and machineries that used to construct the road. This report also looks on the obstruction that happened during construct the road and its solution that had been taken to settle the problems. Type of road construction method that used on the site was explained on this report. The infonnation was gathered and collected through the interview and observations on the site.